The Brazilian Competitiveness Cliff - Canuto, Otaviano; Reis, Jose Guilherme; Cavallari, Matheus (World Bank, Washington, DC, 2014)
Brazilian exports of goods and services have grown sharply in recent years, with sales nearly three times higher in 2010 than in 2000. However, Brazil faces considerable competitiveness challenges: its export performance depends mostly on favorable geographical and sector composition effects. Such challenges increased after the recent global economic crisis. A recent slowdown in industrial exports, production, and investments seems related to supply-side difficulties stemming from a wide range of inefficiencies and rising costs, rather than insufficient demand. Although a stronger currency is one of the factors behind the lower competitiveness of Brazil's manufacturing exports, sluggish productivity performance, lack of dynamism at the firm level, and a real wage uptrend seem to explain a significant part of the overall loss of competitiveness. This diagnostic reinforces the urgency of resuming the agenda of microeconomic reforms, increasing the investment-to-Gross Domestic Product (GDP) ratio, and advancing toward better-skilled human capital.